PTU-183 Sehcat – Cast a Wider Net. (4th June 2013) - Kok, B; Mistry, A; Malhotra, R; Burdsall, J; Hall, M; Ransford, R; Milestone, A
Abstract : Introduction: Bile acid malabsorption (BAM) is a common cause for chronic diarrhoea in patients with risk factors. The diagnosis is usually confirmed by SeHCAT scan demonstrating lack of retention of radiolabelled bile acid. Treatment with bile acid sequestrants may improve diarrhoea symptoms. We report our experience of using SeHCAT in the investigation of patients with chronic diarrhoea and patient response to therapy. Methods: Over a 30 month period January 2009- June 2012, all patients who underwent a SeHCAT scan were identified. Patient records and blood results/radiological imaging/endoscopy procedures performed prior to SeHCAT were reviewed. An abnormal SeHCAT result was defined by bile acid retention < 8%. Equivocal results of 8–15% retention were regarded as normal. Results: 112 patients underwent a SeHCAT scan during this period. 4 patients were excluded due to unavailability of patient records. 53 patients (49%) had abnormal SeHCAT retention. In the remaining 55 patients bile acid retention ranged from 8.1% to 76.8%. BAM was diagnosed in 8 out of 17 patients with a possible Type I abnormality (terminal ileal disease/resection or previous pelvic radiotherapy), 27 out of 66 patients with a possible Type II abnormality (idiopathic) and 18 out of 25 patients with a possible Type III abnormality (post-cholecystectomy). Additional patient demographics are represented in Table 1. The incidence for BAM was highest in the cohort of patients who were post-cholecystectomy, with 71% of all suspected Type III BAM patients having abnormal SeHCAT. However, in terms of absolute numbers, idiopathic BAM formed the highest proportion for abnormal SeHCAT. Interestingly, a wide age variation was experienced across the three groups with proven BAM. The age range in Type I was 36–71 years, in Type II 37–74 years and in Type III 26–80 years. 57% of patients with proven BAM had documented improvement in their diarrhoea frequency and consistency on treatment with a bile acid sequestrant (eg colestyramine). Average reduction of stool frequency was from 7 times/day to 3 times/day. Conclusion: These results show that BAM is a relatively common problem. It occurs for a variety of reasons and should be thought of earlier in the investigative algorithm, independent of age. In our cohort, a history of post-cholecystectomy chronic diarrhoea was the most likely risk factor associated with BAM, hence this group may particularly benefit from earlier use of SeHCAT scan. Clinical response to colestyramine in BAM was high, although data on long-term compliance/response was not available. Disclosure of Interest: None Declared.